Russian aggression against Ukraine: a new challenge facing Antarctic governance - Fedchuk, A.; Cheberkus, D.; Zherebchuk, S. (Ukrainian Antarctic Journal, 2022)
The Antarctic Treaty System has long been seen as an example of successful international cooperation for peace, research, and environmental protection for the benefit of all humanity. However, the military aggression of one Antarctic decision-making state against another has a destructive effect on the latter’s national Antarctic program resulting in a sequestered budget, a reduced research program, and a need to support the scientists threatened or displaced by the warfare. Such military aggression requires a consolidated response from the Antarctic community and challenges the Antarctic Treaty itself as an early and critical arms-control instrument and could undermine the ATS regime. This study examines the first individual and collective efforts to counter Russian full-scale military invasion of Ukraine since February 24, 2022, made by the international polar community, particularly during the highest annual international forum for the Antarctic governance – the 44th Antarctic Treaty Consultative Meeting, ATCM (Berlin, 2022). It is argued that this meeting saw an unprecedented deviation from almost 60 years of diplomatic practices by Antarctic Treaty Parties of controversy avoidance and use of imprecise language in their reports. In Berlin, there was the condemnation in the strongest possible terms of Russian unjustifiable, unprovoked, and illegal invasion of Ukraine. This démarche to the Russian delegation will necessarily affect the further work of other Antarctic-related administrative and advisory bodies within the Antarctic Treaty System. That includes ATCM’s observers and experts’ organisations such as the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR), the Council of Managers of National Antarctic Programs (COMNAP), the Scientific Committee on Antarctic Research (SCAR), and the International Association of Antarctica Tour Operators (IAATO). It is expected that if the aggression continues, isolation measures such as international and national sanctions and institutional restrictions will be extended. In this case, further progress in rejecting any Russian initiatives and suspending ongoing joint projects with Russian partners will significantly complicate the diplomatic, research, fishery, and logistics activities of the Russian Federation within the Antarctic area until the situation allows for the resumption of cooperation.